Effective Communication of Doctors in Hospitals Regarding the Quality of Inpatient Services: A Literature Review - Ulfa Fadhilah Lubis; Ermi G; Sri Lestari Ramadhani Nasution (Journal of Community Health Provision, 2021)
This article discusses the concept of effective Communication of Doctors on the Quality of Inpatient Services. Outpatient and inpatient clinics can both benefit from continuously offering higher-quality care than their competitors. The most important thing is to ensure that patients are satisfied with the service they receive. The services they offer are restricted to what they have learned in medical school, which is only the most fundamental of medical skills. To help patients better grasp their health conditions as well as their options and limitations through verbal and nonverbal communication, doctors work together to come up with creative solutions. An interpreter is required if the doctor and patient don't speak the same language